2017
DOI: 10.1111/gean.12149
|View full text |Cite
|
Sign up to set email alerts
|

Fast Food Data: Where User‐Generated Content Works and Where It Does Not

Abstract: As big urban data usage expands in the social sciences, there remain real concerns about fidelity to on the ground conditions. In this paper, we examine the correspondence between Phoenix metro area restaurants identified by a social media source (http://yelp.com) and those from an administrative source (Maricopa Association of Governments [MAG]). We find that they capture largely disjoint subsets of Phoenix restaurants, with only about one‐third of restaurants in each data set present in the other. Point patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
2
12
0
3
Order By: Relevance
“…This data is not perfect (Wyly 2014;Ash et al 2018), but can be useful with the right theoretical grounding (Shelton et al 2015, 199). Indeed, bias from non-representative samples (Boeing and Waddell 2017;Folch et al 2018;Zhang and Zhu 2018) or spatial disparity in coverage (Shelton et al 2014) is increasingly well studied.…”
Section: The Future Of Areal Datamentioning
confidence: 99%
“…This data is not perfect (Wyly 2014;Ash et al 2018), but can be useful with the right theoretical grounding (Shelton et al 2015, 199). Indeed, bias from non-representative samples (Boeing and Waddell 2017;Folch et al 2018;Zhang and Zhu 2018) or spatial disparity in coverage (Shelton et al 2014) is increasingly well studied.…”
Section: The Future Of Areal Datamentioning
confidence: 99%
“…One aspect of this research includes studying vulnerability to emergencies (Kermanshah, Derrible 2016). The Workplace Area Characteristics files have been used to describe neighborhood character (Folch et al 2017) and to identify business districts (Manduca 2018). The LODES data have also been used for web visualization, including the "Where Are The Jobs?"…”
Section: Examples Of Lehd Data Usementioning
confidence: 99%
“…Another study, that classified restaurants by taste, found associations between restaurants labeled with certain tastes and nearby neighborhood characteristics, such as income, racial composition, and education (23). However, only a couple of studies have used Yelp data in healthy food access research (24,25). These studies demonstrated that Yelp data contained more accurate details on restaurants and healthy food stores than traditional business information sources and commercially available datasets, but had coverage limitations over a metro area.…”
Section: Introductionmentioning
confidence: 99%